Regionalização dos Expressivos Não-Morfológicos dos Estados de Alagoas e Sergipe, Brasil - Ajibola Isau Badiru; Nubia Dias dos Santos (Confins)
The objective was to map the evolution of the rationalized sociological limits to analyze the evolution of state boundaries and processes. The emergence of the States of Alagoas and Sergipe is crossed at different scales along the São Francisco River and is translated as a set of territorial patterns characterized by points, lines and structuring polygons of territorialization determined by the state network. Based on the linearity, convergences and hierarchy of spatial spatial boundaries, the main vectors that actively participate in the regionalization of the topological expressives were identified, which consists of the spatial construction of non-morphological vectors. They are forces of the transfiguration of the dimension of the country that can be decoded for the understanding of the natural and social patterns and processes prescribed in time and space. The location of Sergipe and Alagoas is characterized by interconnections in different zones, involving a set of sociological expressions that confirm the integrated development, affirmed in the ground exactly by points of non-morphological lines of the federal states. The research represents a methodological simplification that dialogues with space-territory, a regionalization of spatial reality, aiming at strategic planning.